The Juridification of Outer Space Environmental Governance under the Concept of a Community of Shared Future for Humankind - Wu, Jia-xin; Baitukayeva, D. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The systemic dilemma in outer space environmental governance stems from the intrinsic transboundary nature of space activities, the rapid iteration of space technologies, and the global commons character of outer space. These factors have produced structural deficiencies within the existing state-centric international space law regime, manifested in regulatory lag and weak enforceability when confronting compound threats such as orbital debris proliferation, the militarization of outer space, and inequitable allocation of extraterrestrial resources. In response, the concept of a ↳community of shared future for humankind should serve as the normative foundation for both rule reconstruction and institutional innovation. Substantively, a shift toward a responsibility-based model of debris governance and a fair benefit-sharing mechanism for space resources is required to fill gaps in material norms. Procedurally, the establishment of mandatory dispute settlement and independent compliance oversight mechanisms is necessary to strengthen institutional guarantees. This approach helps reconcile national interests with the common interests of humanity, promoting a transition in outer space environmental governance from political commitment to a binding, juridified order. Ultimately, it contributes to the development of a more inclusive, effective, and intergenerationally equitable governance paradigm for outer space.